Effect of Humic Acid Supplementation in Feed on The Growth and The Total Number of Bacteria in The Digestive Tract of Catfish (Clarias sp.) - Budi, S.Pi., M.Si, Darmawan Setia (Journal of Aquaculture Science, 2021)
Catfish (Clarias sp.) is one of Indonesia’s leading fishery commodities whose production continues to be increased. Humic acid is known to help increase growth in several types of fish and is expected to be applied to catfish. This study aims to determine the effect of humic acid in commercial feed on the growth and total number of bacteria in the digestive tract of catfish (Clarias sp.). A total of 300 catfish with an average length of 5.76 ± 0.21 cm and an average weight of 27.92 ± 0.39 g were used in 5 treatments (4 replicates/treatments) of humic acid supplementation in feed with different doses, namely P1 (without humic acid/control), P2 (0.5 %), P3 (1.0%), P4 (1.5 %), and P5 (2.0 %). Maintenance was carried out for 40 days by feeding treatment 3 times a day as much as 5% of body weight. Parameters observed were absolute length growth (cm), absolute weight growth (g), specific growth rate (%), and total bacteria in the digestive tract (colonies/g). Based on the results of the study, it was found that the treatment had a significant effect on the growth and number of bacterial colonies with the optimal dose of humic acid of 0.5. Keyword : Behavior, Doses, Control, Colony